HUBUNGAN FAKTOR SOSIODEMOGRAFI DENGAN KEJADIAN GIZI KURANG (UNDERWEIGHT) PADA BALITA DI WILAYAH PESISIR PANTAI NIPAH - Baiq Amira Fatmaharani; Aena Mardiah; Velia Maya Samodra; Artha Budi Susila Duarsa (Jurnal Kesehatan, 2026)
Background: Underweight or insufficient nutrition is a nutritional issue in toddlers that can be detected earlier than stunting and wasting. Early growth disturbances in children are characterized by weight faltering, where the weight does not increase according to standards. If left unaddressed, it can lead to underweight, progress to wasting, and eventually result in stunting. Sociodemographic factors can influence the occurrence of underweight, encompassing educational levels of parents, parental knowledge, family size, and family income. Objective: To determine the relationship between sociodemographic factors and the incidence of underweight among toddlers in the Nipah Coastal Area. Method: This research is a quantitative study using a cross-sectional design. The study population consists of all parents with toddlers in the Nipah Coastal Area, North Lombok Regency, West Nusa Tenggara. Cluster random sampling was used to select the sample. The significance level was set at a p-value of <0.05. Results: The study indicates that there is no significant relationship between the father's educational level (p-value = 0.794), mother's educational level (p-value = 0.686), and family income (p-value = 0.528) with the occurrence of underweight. However, there is a significant relationship between parental knowledge level (p-value = 0.000) and family size (p-value = 0.001) with the occurrence of underweight. Conclusion: Based on the statistical tests conducted, there is a relationship between parental knowledge level, and family size with the incidence of underweight in toddlers in the Nipah Coastal Area. Meanwhile, no relationship was found between the father's educational level, mother's educational level, and family income with the occurrence of underweight in toddlers in the Nipah Coastal Area.